Acute Myocardial Injury and Electrocardiogram Changes in a Case of Aluminum Phosphide Poisoning - Dadpour, Bita; Milani, Nasrin; Mehrpour, Omid; Najari, Fares (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Aluminum phosphide (AIP) poisoning is one of the major causes of mortality among toxic substances. The symptoms and signs of toxicity are nonspecific and related to dose and route of exposure. A 20-year-old woman was admitted to the emergency department due to the consumption of one AIP tablet. ECG was normal at 2 hours post-ingestion and echocardiography revealed LVEF of 55-60% at 4 hours post admission. ECG abnormalities in this patient included VT and VF on the second night. She experienced an unusual rhythm disturbance in term of LBBB and Brugada pattern besides low ejection fraction of left ventricue (about 20-25%) on the third day. The main emphasis for AIP poisoning cases is on a timely, precise and prompt symptomatic treatment.